2019
DOI: 10.1016/j.physbeh.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Early overnutrition alters synaptic signaling and induces leptin resistance in arcuate proopiomelanocortin neurons

Abstract: Early overnutrition disrupts leptin sensitivity and the development of hypothalamic pathways involved in the regulation of metabolism and feeding behavior. While previous studies have largely focused on the development of neuronal projections, few studies have examined the impact of early nutrition on hypothalamic synaptic physiology. In this study we characterized the synaptic development of proopiomelanocortin (POMC) neurons in the arcuate nucleus of the hypothalamus (ARH), their sensitivity to leptin, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In agreement with former studies that indicated an influence of body weight on synaptic plasticity [ 16 , 18 , 19 , 20 , 21 , 23 ], we observed that postnatal overnutrition further increases the presynaptic excitatory transmission to ARH LepR-expressing cells, beyond the rise already observed with puberty. Suggesting that early weight gain affect other brain nuclei which send projections to ARH LepR-expressing neurons.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with former studies that indicated an influence of body weight on synaptic plasticity [ 16 , 18 , 19 , 20 , 21 , 23 ], we observed that postnatal overnutrition further increases the presynaptic excitatory transmission to ARH LepR-expressing cells, beyond the rise already observed with puberty. Suggesting that early weight gain affect other brain nuclei which send projections to ARH LepR-expressing neurons.…”
Section: Discussionsupporting
confidence: 93%
“…Age-dependent synaptic plasticity has been described in ARH neurons, as well as in neurons of the paraventricular nucleus of the hypothalamus [ 16 , 17 , 21 , 34 , 35 ]. For example, ARH kisspeptin neurons exhibit a lower presynaptic inhibitory tone after puberty onset [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain slices were collected as previously described (30). The forebrain and brainstem were mounted adjacent to each other and sectioned simultaneously with a sapphire knife (Delaware Diamond Knives) yielding roughly three slices from each region (250-mm) per mouse.…”
Section: Brain Slice Electrophysiologymentioning
confidence: 99%